CONDITION OF THE HEMOSTASIS SYSTEM IN PATIENTS WITH ADENOMA AND PROSTATE CANCER CANCER - Ekaterina Victorovna Alymova; Olga Valentinovna Smirnova; Eduard Vil’yamovich Kasparov; Nadezhda Mitrofanovna Titova (Siberian Journal of Life Sciences and Agriculture, 2019)
161 men aged 45 to 83 years old with a different stage of the disease were examined. Among the surveyed, three groups were distinguished: patients with prostate adenoma – 46 patients, a group of patients with prostate cancer – 53 patients, the comparison group – 48 relatively healthy men of the same age category. All patients underwent biochemical blood tests with the definition of hemostasis system components that characterize all parts of the blood coagulation system: APTT, PT, PI, INR, blood fibrinogen level, thrombin time.The purpose of the study is to identify the features of the hemostatic system in patients with adenoma and prostate cancer.